Microbiological Outcomes Associated With Low Leukocyte Counts in Cerebrospinal Fluid. (5th December 2020) - Wald, Mathieu; Merisor, Simona; Zachary, Pierre; Augereau, Olivier; Gravier, Simon; Jaulhac, Benoit; De Briel, Dominique; Velay, Aurélie; Gregorowicz, Guillaume; Martinot, Martin
Abstract: The significance of low leukocyte counts in cerebrospinal fluid (CSF) remains unclear. We performed a 2-year retrospective study to examine microbiological outcomes associated with CSF leukocytes at 6–10/mm 3 . Of the 178 samples examined, we detected positive results for 11 samples, including 5 cases of tick-borne encephalitis virus infection.